PROFIL KEPERCAYAAN DIRI SISWA TINGKAT VIII SMP NEGERI 3 CIMAHI - Munfaati, Agnia; Irmayanti, Rima; Yusnita Fitrianna, Aflich (FOKUS : Kajian Bimbingan dan Konseling dalam Pendidikan, 2025)
This study aims to determine the profile of self-confidence of students in level VIII of SMP Negeri 3 Cimahi. This study used a descriptive quantitative approach with data collection techniques in the form of a self-confidence questionnaire given to 74 students from two classes, namely classes VIII-F and VIII-A. The results showed that the profile of self-confidence in level VIII students of SMP Negeri 3 Cimahi based on aspects of confidence in their abilities, most students were in the high category, as many as 39 students with a percentage of 53%. Meanwhile, of the five aspects that are most in the very low category, namely in the rational and realistic aspects, there are 13 students with a percentage of 18%. based on the results of the graph, it shows that female students are more in the very low category, totaling 7 while male students are 4 in the very low category. In addition, the difference between classes based on the results of the graph shows that class VIII-A with a percentage of 50.7% and class VIII-F 49.3%. Looking at these results confirms that there is a need for customized strategies to increase student confidence, according to the unique conditions of each class.